The Effectiveness Of Word Of Mouth Communication Through Whatsapp Media In Increasing Tourist Visits (Study Of Bridal Waterfall Attractions Bengkulu Tengah Regency) - Bella Rena Anjelina; Vethy Octaviani; Sapta Sari (Penerbit Jurnal Indonesia, 2022)
The purpose of this research is to find out the effectiveness of word of mouth communication through WhatsApp media in increasing tourist visits. In this study, researchers used qualitative research methods. The object of research is the Bride Waterfall Tour which is located in Bukit Bengkulu Tengah Village. The key informants in this research were the Head of Bukit Village, Karang Taruna, the Entrance Guard, the main informants were visitors. The results of this study are that Word Of Mouth Communication through Whatsapp media in increasing tourist visits is quite effective as a promotional medium in increasing visitor interest. The level of success of Word Of Mouth Communication in increasing tourist visits to Bridal Waterfall through social media as a means of promotion can be seen from the fulfillment 5 elements of Effectiveness according to (Jalaludin Rakhmat, 2008:45), namely 1. visitors understand the purpose of posting on Whatsapp Media which aims to invite tourists to come visit, 2. Pleasure where visitors who see posting photos of beautiful waterfall views are accompanied by photo spots those who are interested are interested in coming to visit the Bridal Waterfall immediately, 3. Affecting the attitude in which visitors search for information on the whereabouts of the Bridal Waterfall, 4. This improves social relations where visitors invite friends or family to go visit together, 5. Follow up I want to visit the location of the bridal waterfall and enjoy the view immediately. The results of the author's observations show evidence of the number of tourists who come to visit each month as seen from the number of WhatsApp posts or snaps that leave an impression on visitors in the form of photos or videos.